The role of magnetic resonance imaging (MRI) in focal therapy for prostate cancer: recommendations from a consensus panel. (13th November 2013) - Muller, Berrend G.; Fütterer, Jurgen J.; Gupta, Rajan T.; Katz, Aaron; Kirkham, Alexander; Kurhanewicz, John; Moul, Judd W.; Pinto, Peter A.; Rastinehad, Ardeshir R.; Robertson, Cary; de la Rosette, Jean; Sanchez‐Salas, Rafael; et al.
Abstract : Objective: To establish a consensus on the utility of multiparametric magnetic resonance imaging (mpMRI) to identify patients for focal therapy. Methods: Urological surgeons, radiologists, and basic researchers, from Europe and North America participated in a consensus meeting about the use of mpMRI in focal therapy of prostate cancer. The consensus process was face‐to‐face and specific clinical issues were raised and discussed with agreement sought when possible. All participants are listed among the authors. Topics specifically did not include staging of prostate cancer, but rather identifying the optimal requirements for performing MRI, and the current status of optimally performed mpMRI to (i) determine focality of prostate cancer (e.g. localising small target lesions of ≥0.5 mL), (ii) to monitor and assess the outcome of focal ablation therapies, and (iii) to identify the diagnostic advantages of new MRI methods. In addition, the need for transperineal template saturation biopsies in selecting patients for focal therapy was discussed, if a high quality mpMRI is available. In other words, can mpMRI replace the role of transperineal saturation biopsies in patient selection for focal therapy? Results: Consensus was reached on most key aspects of the meeting; however, on definition of the optimal requirements for mpMRI, there was one dissenting voice. mpMRI is the optimum approach to achieve the objectives needed for focal therapy, if made on a high quality machine (3T with/without endorectal coil or 1.5T with endorectal coil) and judged by an experienced radiologist. Structured and standardised reporting of prostate MRI is paramount. State of the art mpMRI is capable of localising small tumours for focal therapy. State of the art mpMRI is the technique of choice for follow‐up of focal ablation. Conclusions: The present evidence for MRI in focal therapy is limited. mpMRI is not accurate enough to consistently grade tumour aggressiveness. Template‐guided saturation biopsies are no longer necessary when a high quality state of the art mpMRI is available; however, suspicious lesions should always be confirmed by (targeted) biopsy.